(untitled) (Pharmacology & Toxicology Research (ISSN 2349-4581), 2024)
Plants and their derivatives played a key role in world health and have long been known to possess biological activity. The importance of biological evaluations of plants derived agents used in the treatment of various diseases. The data of the acute toxicity studies (oral) on medicinal plants obtained in order to increase the confidence in its safety to human, particularly for use in the development of pharmaceuticals. The aim of this work was to study the effects of repeated dosage of two concentration of plant extracts such as 400mg/kg and 600mg/kg were administered to Swiss albino mice daily for 15 days (orally) to check the safety profile of plant extracts. Mice were randomly selected and each group contains three animals, and analyse the physical parameters, biochemical parameters and liver toxicity were studied at the end of the experiment and analyse the histopathological studies to done for 400mg/kg of group animals assess any organ specific toxicity. From the study there was no changes were observed in liver section when compared with treated and control groups.